Design of a waste collector cart with manual control - Zambri, Daniel Hakim (2025)
The Waste Collector Cart (WCC) introduces an innovative solution to the pressing challenges of waste cleaning in inaccessible and hazardous environments, aiming to reduce both the manpower required for garbage collection and reduce the accumulation of waste debris in the environment. This project's objective is to fabricate a mini car that has the capability to move around with manual control and to pick up waste on the ground effectively. The WCC incorporates manual control which enables the operator to remotely control the WCC's movements and supervise garbage collection tasks in real-time. At the heart of the WCC lies its garbage collection system, consisting of a conveyor roller mechanism that has brushes mounted on the conveyor. This empowers the car to efficiently pick up the garbage into the plastic in the storage unit. By having all these abilities, the WCC is expected to reduce the amount of accumulated waste by cleaning the streets, public spaces, or industrial spaces and navigate narrow alleys and other places where humans can't reach and minimize the amount of manpower needed. To summarize, the Waste Collector Cart represents a transformative advancement in waste management technology, offering a practical and sustainable solution for addressing the complexities of garbage collection in challenging environments